Vanadium allergy following total knee arthroplasty. (18th January 2018) - Peat, Fidel; Coomber, Ross; Rana, Adnan; Vince, Alastair
Abstract : Allergic reactions to metals following joint arthroplasty represent a rare and poorly understood phenomenon. Much is still unknown regarding the natural history of this complication, and how it can best be prevented and managed. We present a case of a 68-year-old woman who underwent a left total knee arthroplasty for treatment of osteoarthritis. After an initial uneventful postoperative course, she developed a troublesome erythematous rash both around the incision site and over her trunk. Blood testing revealed no evidence of infection and clinically her prosthesis was functioning well. Skin patch testing revealed positive results for vanadium (+) and palladium (+). Her cutaneous symptoms are currently being managed conservatively and have shown a partial response to topical steroids. Revision surgery remains a long-term treatment option should conservative therapy fail; however, it would require a custom-made prosthesis as no standard tibial component is free from vanadium.